Linguistic and Cultural Challenges Faced by Translators - Sathisha, Mukta (International Journal of Psychosocial Rehabilitation, 2020)
This article attempts to highlight some of the problems faced by translators when the target language belongs to an entirely different culture from the source language. Every society has its own religious, cultural, economic, political, military and scientific parameters. Translations and translators have a significant role in intercultural translation. It is often said that language is the road map to the culture of a particular state, country or region. During intercultural translation, many different processes of cross language interaction take place. The study of intercultural translation brings forth how we come to know other ways of doing various activities, customs, traditions, methods of celebrating festivals and conversations among people in societies and cultures which are alien to the translator. This paper tries to offer possible solutions to challenges faced by translators during intercultural translation so that they can not only produce an acceptable but a competent translation.